DINAMIKA KEWARGANEGARAAN DIGITAL DI ERA PRABOWO: RESPONS NETIZEN DI X TERHADAP RUU TNI - Taqiya Nadiyatu Kamila; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
The controversy surrounding the revision of the Indonesian National Armed Forces Law (RUU TNI) in 2025 triggered widespread debate in digital public spaces, particularly on the social media platform X. This study aims to analyze the dynamics of digital citizenship actions expressed by citizens in online discussions related to the RUU TNI controversy. The research employs the framework of acts of digital citizenship developed by Isin and Ruppert to understand how citizens perform political participation through digital communication practices. This study adopts a qualitative approach using digital ethnography combined with in-depth interviews. The research data consist of 265 posts collected from X during the period of 11–20 March 2025, as well as interviews with social media users involved in the discussion. The findings reveal five forms of digital citizenship actions: calling, opening, closing, witnessing, and flaming. These actions illustrate how citizens demand political accountability, construct collective interpretations of policy issues, and express moral judgments toward political actors. The study demonstrates that social media functions as an alternative arena of political participation when formal political processes are perceived as lacking transparency and public engagement.